Proceedings of the 29th ACM International Conference on Information &Amp; Knowledge Management 2020
DOI: 10.1145/3340531.3411965
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Adaption for Demand Prediction based on Multi-task Memory Neural Network

Abstract: Accurate demand forecasting of different public transport modes (e.g., buses and light rails) is essential for public service operation. However, the development level of various modes often varies significantly, which makes it hard to predict the demand of the modes with insufficient knowledge and sparse station distribution (i.e., station-sparse mode). Intuitively, different public transit modes may exhibit shared demand patterns temporally and spatially in a city. As such, we propose to enhance the demand p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 27 publications
(48 reference statements)
0
8
0
Order By: Relevance
“…For example, one study developed a knowledge adaptation module that boosted the prediction of transportation modes with fewer stations (e.g., ferries) by adapting the demand pattern from station-intensive modes (e.g., buses). The model results show that MTL improves the demand forecasting performance for modes with fewer stations [10]. Another study we found looked into demand prediction for the subway and TNCs [40].…”
Section: Multi-task Learningmentioning
confidence: 87%
See 1 more Smart Citation
“…For example, one study developed a knowledge adaptation module that boosted the prediction of transportation modes with fewer stations (e.g., ferries) by adapting the demand pattern from station-intensive modes (e.g., buses). The model results show that MTL improves the demand forecasting performance for modes with fewer stations [10]. Another study we found looked into demand prediction for the subway and TNCs [40].…”
Section: Multi-task Learningmentioning
confidence: 87%
“…Recently, multi-task learning (MTL) has garnered significant attention in the AI domain, as it enables different tasks to share information, thereby enhancing the prediction accuracy. Some transportation demand forecasting research has also adopted this technique [10][11][12][13][14]. However, the majority of these studies allow information sharing between tasks without controlling for "negative transfer", which is common and could reduce the effectiveness of multi-task learning.…”
Section: Introductionmentioning
confidence: 99%
“…MasterGNN [12] utilizes a heterogeneous recurrent GNN to capture the spatio-temporal correlation between air quality and weather monitor stations. MATURE [18] and KA2M2 [19] propose to predict transportation mode with multi-task methods.…”
Section: Related Workmentioning
confidence: 99%
“…Ke et al (2021) focuses on the demand of ride-hailing systems to predict solo and shared service rides jointly by constructing multi-graph convolutional networks. Furthermore, Li et al (2020b) designs a recurrent network for demand prediction of the station-intensive travel mode and the station-sparse travel mode simultaneously to improve the forecasting accuracy for the station-sparse mode. A larger range of different transport modes are explored in Toman et al (2020), including taxis, bikes, subways, and vehicles operated by transit network companies (TNCs).…”
Section: Demand Forecasting Under Multiple Travel Modesmentioning
confidence: 99%